2005
DOI: 10.1016/j.joca.2005.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of human knee meniscus cell phenotype

Abstract: These results demonstrate that the human meniscus is populated by different cell types which can be identified by a distinct CAM composition and membrane marker expression. Unlike the monolayer culture conditions, the alginate culture conditions appear to favor a more fibrochondrocyte-like cell accumulating a CAM resembling the native tissue composition. This CAM composition is distinctly different from the CAM composition of phenotypically stable articular cartilage chondrocytes cultured in the same alginate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
171
0
15

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(191 citation statements)
references
References 44 publications
(46 reference statements)
5
171
0
15
Order By: Relevance
“…49,51 Relevant to the present approach, increased production of proteoglycan and type-II collagen has been documented in aggregate cultures of human meniscal cells treated by FGF-2 in the presence of transforming growth factor beta, 20 a factor well known for its metabolic properties in the meniscus. [24][25][26][27]31,37 Application of combinations of mitogenic and anabolic factors that also include insulin-like growth factors I and II, 18 platelet-derived growth factor, 19,21-23 bone morphogenic proteins 2 and 7, 22,23 and hepatocyte growth factor 22 may thus be of additonal value to improve the healing of meniscal lesions. Alternatively, factors such as the vascular endothelial growth factor, 52 hepatocyte growth factor, 22,33 and platelet-derived growth factor 22 might be considered with FGF-2 53 for their therapeutic effects on cell migration and vasculogenesis.…”
Section: Metabolic Responses Of Human Meniscal Fibrochondrocytes To Fmentioning
confidence: 99%
See 1 more Smart Citation
“…49,51 Relevant to the present approach, increased production of proteoglycan and type-II collagen has been documented in aggregate cultures of human meniscal cells treated by FGF-2 in the presence of transforming growth factor beta, 20 a factor well known for its metabolic properties in the meniscus. [24][25][26][27]31,37 Application of combinations of mitogenic and anabolic factors that also include insulin-like growth factors I and II, 18 platelet-derived growth factor, 19,21-23 bone morphogenic proteins 2 and 7, 22,23 and hepatocyte growth factor 22 may thus be of additonal value to improve the healing of meniscal lesions. Alternatively, factors such as the vascular endothelial growth factor, 52 hepatocyte growth factor, 22,33 and platelet-derived growth factor 22 might be considered with FGF-2 53 for their therapeutic effects on cell migration and vasculogenesis.…”
Section: Metabolic Responses Of Human Meniscal Fibrochondrocytes To Fmentioning
confidence: 99%
“…14,15 Delivery of therapeutic genes in the meniscus is an attractive approach to enhance meniscal repair. 16,17 Candidate factors that stimulate the cellular activities of meniscal fibrochondrocytes include the insulin-like growth factors I and II, 18 fibroblast growth factor 2 (FGF-2), [18][19][20] platelet-derived growth factor, 19,[21][22][23] transforming growth factor beta, [23][24][25][26][27] hepatocyte growth factor, 22 and the bone morphogenic proteins 2 and 7. 22,23 Although several studies have been performed to evaluate the efficacy of nonviral and viral vectors to deliver reporter genes in meniscal cells in vitro, [28][29][30][31][32][33][34] in situ, 30,35 and in vivo, 30,34,36 little is known about the value of applying therapeutic gene sequences in the injured meniscus.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Tissue engineering has recently been proposed as a possible solution for meniscal regeneration. 15,[24][25][26][27][28] There have, however, been very few animal studies reported in the literature that have investigated the possibility of using cells in a partial or total meniscal substitute. 15, 24 Walsh et al 25 used a collagenous sponge loaded with mesenchymal stem cells to heal a partial meniscus defect in rabbits and reported that the presence of cells augmented the repair process but did not prevent degenerative osteoarthritis.…”
Section: Introduction Lmentioning
confidence: 99%
“…CD34 marker expression was found to be absent in both the control and UCM supplemented meniscal cells indicating that the UCM does not induce any differentiation during the proliferation. CD34 has been reported to be expressed as surface antigen in lympho hematopoietic stem cells and progenitor cells (Verdonk et al 2005). The fibrochondrocyte cells present in the inner surface of the meniscus do not show any CD34 markers on surface.…”
Section: Discussionmentioning
confidence: 97%